Theoretical and experimental research of hot rolling of aluminum strips for solar collector - Makeeva, A.S.; Kuzmenko, O.S.; Remez, O.A.; Frolov, Ya.V.; Uwarow, I.; Gridin, O.Yu. (Геотехнічна механіка, 2016)
The article investigates the process of rolling aluminum strips with aluminum wire inside for the solar collector components. The closure of coal mines, the constant rise in the cost of oil and gas compel to refer to the methods for producing renewable (alternative) energy. An urgent problem is the enhancement of solar manufacturing technologies in order to improve the quality and reduce the cost of products. The article presents the results of experimental and theoretical studies of the hot rolling process of aluminum strips with aluminum wire between them for internal collector channels. The velocity fields were researched; dependence on the rolling load changes for different degrees of deformation was obtained. It was found that for obtaining high-quality welding strips with wire between them the degree of deformation should be more than 35%. The comparison of the dependencies obtained experimentally and with the theoretical calculations was carried out, which showed a high degree of similarity. The comparison of the dependences obtained experimentally with the theoretical calculations was carried out, which showed a high degree of reproducibility, repeatability and similarity. Scientific novelty of the research lies in the parameters justification of hot rolling process of two aluminum strips with aluminum wire between them for partial welding of aluminum strips. These results can be used in industrial processes for the parts production of solar collectors in alternative energy. This study was supported by German Academic Exchange Service (DAAD) in the framework of German-Ukrainian project «Praxispartnershaft Metalurgie».